Water bodies created by peatland restoration are potential habitats for amphibians and reptiles - Susanne Stückler; Ria Sonnleitner; Silke Schweiger (Herpetozoa)
In Lower Austria’s Waldviertel region, artificial drainage ditches were constructed in the last century in order to use peatlands for forestry, agriculture, and peat extraction. By now, many of these peatlands are part of the Natura 2000 network and therefore gradually undergo restoration measures, which aim to rewet the peatlands. For this, the ditches are blocked with wooden dams, leading to a water runback, which in turn fills the ditches and peat pools. Such artificial water bodies generally depict secondary habitats for many species. Here, we investigated the amphibian fauna in four restored peatlands in the Waldviertel region and measured abiotic factors of the aquatic habitats to answer the question whether blocked ditches and peat pools are valuable secondary habitats for amphibians. We characterized the microhabitats of amphibians based on various structures and vegetation. Additionally, this study provides a basic assessment of reptile species in the investigated peatlands. During our assessment, we observed 1520 individuals of eight amphibian species, 64 individuals of four reptile species, and characterized 12 different microhabitats. Despite the low pH values of 3.2–4.2, four amphibian species and amphibian spawn were detected in Schwarzes Moos. Our results indicate that peat pools, drainage ditches, and open moorlands are potential habitats for amphibians and reptiles, making their conservation and management an important factor in the protection of amphibian and reptile species.